The Geometry Of Preposition Meanings - Peter Gärdenfors (Baltic International Yearbook of Cognition, Logic and Communication, 2015)
This article presents a unified approach to the semantics of prepositions based on the theory of conceptual spaces. Following the themes of my recent book The Geometry of Meaning, I focus on the convexity of their meanings and on which semantic domains are expressed by prepositions. As regards convexity, using polar coordinates turns out to provide the most natural representation. In addition to the spatial domain, I argue that for many prepositions, the force domain is central. In contrast to many other analyses, I also defend the position that prepositions have a central meaning and that other meanings can be derived via a limited class of semantic transformations.
Keywords: semantics of prepositions; semantics; geometry of meaning; meaning; semantic domains; spatial domain; prepositions; semantic transformations